2012
DOI: 10.1371/journal.pone.0037039
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microRNA Lethal-7a in the Regulation of Embryo Implantation in Mice

Abstract: MicroRNAs interact with multiple mRNAs resulting in their degradation and/or translational repression. This report used the delayed implantation model to determine the role of miRNAs in blastocysts. Dormant blastocysts in delayed implanting mice were activated by estradiol. Differential expression of 45 out of 238 miRNAs examined was found between the dormant and the activated blastocysts. Five of the nine members of the microRNA lethal-7 (let-7) family were down-regulated after activation. Human blastocysts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 73 publications
3
84
0
Order By: Relevance
“…miR-34c, which is also present in humans, mice and bull sperm (Amanai et al 2006, Krawetz et al 2011, Stowe et al 2014, was detected in all the three libraries from pig ejaculated sperm, epididymal sperm and seminal plasma, indicating that this miRNA species is highly conserved across mammals and confirming that it plays a significant biological role in spermatogenesis or in early embryonic development. We also found that three miRNAs (ssc-let-7a, ssc-miR26a and ssc-miR-10b) were shared in the top 10 most abundant miRNAs in the three libraries, and one of them (miR-let-7a) was detected in mouse epididymal sperm and human seminal plasma (Liu et al 2012a, Wu et al 2012, Cheong et al 2014) and shown to be involved in the regulation of embryo implantation in mice (Liu et al 2012a, Cheong et al 2014). Furthermore, the expression level of let-7a in human seminal plasma was significantly associated with male infertility (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…miR-34c, which is also present in humans, mice and bull sperm (Amanai et al 2006, Krawetz et al 2011, Stowe et al 2014, was detected in all the three libraries from pig ejaculated sperm, epididymal sperm and seminal plasma, indicating that this miRNA species is highly conserved across mammals and confirming that it plays a significant biological role in spermatogenesis or in early embryonic development. We also found that three miRNAs (ssc-let-7a, ssc-miR26a and ssc-miR-10b) were shared in the top 10 most abundant miRNAs in the three libraries, and one of them (miR-let-7a) was detected in mouse epididymal sperm and human seminal plasma (Liu et al 2012a, Wu et al 2012, Cheong et al 2014) and shown to be involved in the regulation of embryo implantation in mice (Liu et al 2012a, Cheong et al 2014). Furthermore, the expression level of let-7a in human seminal plasma was significantly associated with male infertility (Wu et al 2012).…”
Section: Discussionmentioning
confidence: 73%
“…The functional significance of some miRNAs still seems to be compelling, although it is now commonly accepted that small RNAs play a pivotal role in fertilization and embryonic development (Liu et al 2012a, Chen et al 2016a,b, Yuan et al 2016). An early study suggested that sperm-borne miRNAs play a restricted role in mammalian fertilization (Amanai et al 2006); however, a subsequent study suggested that miRNAs play an important role in fertilization and pre-implantation embryonic development .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Let-7 repression in blastocysts facilitates embryo implantation in the mouse (57,58). Proper regulation of expression of IL-10 in trophoblasts and uterine immune cells has been implicated in placental health and fetal development (59).…”
Section: Discussionmentioning
confidence: 99%